Understanding Academic Transport Emissions - Insights from an Italian Medium-Size Public University - Anna Claudia Caspani; Elena Maggi; Michela Rosselli (Universitas Diponegoro, 2025)
Universities play a significant role in advancing sustainability and achieving carbon neutrality. This study presents a case analysis of an Italian medium-size university located in Lombardy, focusing on the assessment of CO₂ emissions from the transport sector, with particular attention to commuting patterns as a significant source. By applying standardized methodologies and survey data, the research estimates CO₂ emissions and evaluates the potential for reduction through targeted policies, considering self-reported willingness to adopt sustainable transport modes incentivized by specific interventions. Results show that commuting substantially contributes to the university’s carbon footprint, underscoring the need for integrated mobility strategies that combine environmental, social, and economic benefits. The study highlights the university’s potential as a catalyst for behavioral change and innovation in sustainable transport, offering scalable solutions that improve wellbeing, accessibility, and institutional reputation, while delivering positive impacts both within and beyond the campus community. These findings provide actionable insights and a replicable model for universities aiming to reduce their environmental impact and progress toward carbon neutrality through innovative, data-driven sustainability governance.